PENGARUH PERAN GURU DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR AKUNTANSI SISWA SMA ISLAM 1 SURAKARTA - Kholifah, Siti Nur; Santoso, Sigit; ., Jaryanto (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThe objectives of this research are to study: (1) the effect of teacherâs role on the learning achievement in Accounting of Islam Senior Secondary School 1 of Surakarta; (2) the effect of learning facility on the learning achievement in Accounting of Islam Senior Secondary School 1 of Surakarta; (3) the effects between the teacherâs role and the learning facility on the learning achievement in Ac-counting of Islam Senior Secondary School 1 of Surakarta. This research used the quantitative meth-od with the causal relations. The results of research are (1) there is a positive and significant effect of the teacherâs role on the studentsâ learning achievement in Accounting as indicated by the value of the tstat 4.626 > that of the tcrit. 1.679, (2) there is a positive and significant effect of the learning facility on the studentsâ learning achievement in Accounting as proven by the value of the tstat 4.113 > that of the tcrit. 1.679, and (3) there is a positive and significant effects between the teacherâs role and the learning facility on the studentsâ learning achievement in Accounting as signified by the value of the Fstat 43.377 > Fcrit 3.20.Keywords: Teacherâs role, learning facility, learning achievement in AccountingABSTRAKPenelitian ini bertujuan untuk mengetahui (1) pengaruh peran guru terhadap prestasi belajar akuntansi siswa SMA Islam 1 Surakarta; (2) pengaruh fasilitas belajar terhadap prestasi belajar akuntan-si siswa SMA Islam 1 Surakarta; dan (3) pengaruh peran guru dan fasilitas belajar terhadap prestasi belajar akuntansi siswa SMA Islam 1 Surakarta. Penelitian ini termasuk penelitian kuantitatif hubungan kausal. Hasil penelitian menunjukkan bahwa (1) peran guru berpengaruh positif dan signifikan terhadap prestasi belajar akuntansi dengan nilai thitung sebesar 4,626 > ttabel sebesar 1,679, (2) fasilitas belajar ber-pengaruh positif dan signifikan terhadap prestasi belajar akuntansi dengan nilai thitung sebesar 4,113 > ttabel sebesar 1,679, (3) peran guru dan fasilitas belajar berpengaruh positif dan signifikan terhadap pres-tasi belajar akuntansi dengan nilai Fhitung sebesar 43,377 > Ftabel sebesar 3,20.Kata Kunci : peran guru, fasilitas belajar, prestasi belajar akuntansi